1996
DOI: 10.2323/jgam.42.517
|View full text |Cite
|
Sign up to set email alerts
|

Detection and production of extracellular collagenolytic enzyme from Zygosaccharomyces rouxii.

Abstract: Microbial collagenases are proteinases that are capable of hydrolyzing native collagen in vitro under physiological conditions ( 7) . Production of collagenase or collagenase-like proteases from various bacteria have been reported by many workers. Among the collagenase-producing bacteria, Clostridium histolyticum is the most studied microorganism and crude or purified collagenase from this bacteria are now available commercially. There have been works published on collagenase from the mold Trichophyton shoenle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Some studies involving bacteria indicate that adding gelatin or casein in the medium increases the collagenase yield. However, the work of Ok and Hashinaga 48 with Z. rouxii yeast, observed that adding gelatin in YPG medium was not essential for the production of collagenase. Lima et al 24 reported the use of a inexpensive culture medium for P. aurantiogriseum collagenase production, using soy flour as main substrate, and the same medium was used by authors Lima et al, 58 reaching one of the best collagenolytic activity values found during this review (Table 3).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies involving bacteria indicate that adding gelatin or casein in the medium increases the collagenase yield. However, the work of Ok and Hashinaga 48 with Z. rouxii yeast, observed that adding gelatin in YPG medium was not essential for the production of collagenase. Lima et al 24 reported the use of a inexpensive culture medium for P. aurantiogriseum collagenase production, using soy flour as main substrate, and the same medium was used by authors Lima et al, 58 reaching one of the best collagenolytic activity values found during this review (Table 3).…”
Section: Resultsmentioning
confidence: 98%
“…For the best results regarding collagenolytic activity, Lima et al 58 and Mahmoud et al, 53 the optimum pH of the enzyme was not evaluated. Ok and Hashinaga 48 evaluated the optimal pH (8.2) of the enzyme produced by Z. rouxii yeast. Lima et al 24 found that pH of 9.0 was the best for collagenolytic enzyme produced by P. aurantiogriseum .…”
Section: Resultsmentioning
confidence: 99%
“…This value is much higher than other published results. Baehaki et al [35] achieved a specific activity of 0.546 U/mg, with Bacillus licheniformis; Jain and Jain [1] [37], 70.4 U/mg with Zygosaccharomyces rouxii, all of them with more than 15 times lower activity than the produced by Penicillium sp. UCP 1286.…”
Section: Enzyme Production Kineticsmentioning
confidence: 99%
“…Lima et al [9] showed that the enzyme produced by P. aurantiogriseum was very active at the pH range 8 to 10, and the highest activity occurred at pH 9.0, as in the present work. Ok and Hashinaga [37] related that optimum pH to collagenase produced by Zygosaccharomyces rouxii was 8.2. Only the enzyme produced by Rhizoctonia solani was produced under acid pH (5.0) [14].…”
Section: Effect Of Ph On Collagenolytic Activity and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation